Evaluation of the response of cortisol, corticotropin and blood platelets kinetics after laparoscopic and open cholecystectomy - Crema,Eduardo (2005)
PURPOSE: To compare the behavior of serum cortisol and ACTH levels and platelet kinetics after laparoscopic and open cholecystectomy. METHODS: In this prospective study, 31 patients with symptomatic cholelithiasis submitted to elective cholecystectomy, 17 by the laparoscopic route and 14 by the open route, were compared. Peripheral blood samples were collected on admission of the patient, during anesthetic induction, and 2, 6, 12, 24 and 48 hours after the surgical incision. Platelets were counted in hematoxylin-eosin-stained specimens under a light microscope at 100X magnification. Cortisol and ACTH were measured by chemiluminescence. RESULTS: Cortisol and ACTH levels showed a significant increase (p<0.05) within the first hours after surgery compared to preoperative values. At 2 hours, a significantly higher cortisol concentration was observed in the laparoscopic group compared to the open surgery group (p=0.0365). A return to basal levels during the later postoperative periods (24 and 48 hours) was only observed for ACTH, while serum cortisol continued to be elevated during the same period, being significantly higher in the open surgery group than in the laparoscopic group (p24 = 0.0248 and p48 = 0.032). Different platelet response curves were obtained for the two groups, but their levels were normal at all times studied. No significant difference (p>0.05) between the post- and preoperative periods was observed for either group. CONCLUSION: A hormonal response was observed for both procedures studied, but the surgical stress was higher and longer lasting in open surgery compared to the laparoscopic approach. However, no significant variation in platelet kinetics in response to tissue injury was observed between the two procedures.